Delayed, diffuse acute peritonitis secondary to misplacement of a cystogastrostomic “pigtail” drain in an outpatient after discharge - Costi, Renato; Zarzavadjian Le Bian, Alban; Mita, Maria Teresa; Brou Fulgence Kassi, Assamoi; Sarli, Leopoldo; Violi, Vincenzo (Acta Biomedica Atenei Parmensis, 2018)
Background and aim of the work: Pancreatic pseudocyst endoscopic drainage by pancreatogastrostomy “pigtail” drain placement is spreading worldwide, with high success-rate and low morbidity, and is increasingly performed as outpatient procedure. The paper reports an unusual very early complication of this procedure and discusses the peculiar aspects of this event in an outpatient setting. Methods: The first case of a 56-year-old outpatient developing a postoperative diffused acute peritonitis by gastric juice spilling caused by the  misplacement of the distal end of two transgastric drains not reaching the pseudocyst is reported. As the case was programmed as outpatient and acute peritonitis symptoms occurred eight hours postoperatively, the patient was discharged and rehospitalized. A review of the literature of rare perforative complications of pancreatogastrostomy is performed. Results: CT scan allowed the prompt diagnosis, as it showed massive pneumoperitoneum, free fluid collection, and pigtail drain misplacement. Emergency laparoscopy allowed the removal of the two misplaced drains and gastric reparation. The procedure lasted 65 minutes, mostly needed for lavage. The patient was discharged 5 days later and outcomes are unremarkable 7 months after the procedure. Conclusion: The indication to endoscopic pancreatogastrostomy and its outpatient management should be carefully pondered. Pancreogastrostomy drain misplacement may cause a life-threatening acute peritonitis associated with early aspecific symptoms, resulting in a challenging situation, especially in an outpatient setting. CT-scan may allow prompt diagnosis and effective management by minimally invasive surgery.